World communism : a history of the Communist International - Borkenau, Franz; Aron, Raymond (Michigan : University of Michigan Press, 1962)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Komintern; Derde Internationale (1919-1943).; communisme